ANALISIS KERAGAMAN PRODUK DAN KEPERCAYAAN YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA E-COMMERCE LAZADA DI KOTA BATAM - Simanjuntak, Jackhon Pahala; Robert Situmorang; Rikson Pandapotan Tampubolon (Jurnal PROFITA : Akuntansi dan Manajemen, 2025)
Thanks to the development of technology and information, buying and selling activities can also be carried out in a network or E-Commerce which provides many solutions to problems, the main one being mobility. The seller is not required to rent a shop and can show the shop window in the form of a photo, then the buyer also does not need to travel to make a purchase or even when he wants to inquire about a particular product plus the range that can be traced by the buyer provides more options without any emphasis. price. The choice of Lazada as a buyer's choice in shopping online certainly has main causes and factors. There are many factors that determine purchas decision. That studies aims to determined the effects of products diversity,and trust on employee purchase decision at Lazada online in Batam city. The technique in collecting data is by distributing questionnaires to 385 respondents, namely people who use the Lazada application. The results of his research that product diversity and trust partially and simultaneously has a significant effects on purchase decision.